- PRAKTIK GLOKALISASI MELALUI MEDIA SOSIAL INSTAGRAM DALAM UPAYA MEMBANGUN CITRA PARIWISATA DESA TENGANAN PEGRINGSINGAN: - - Putu Sri Handayani; Ayu Nanda Krisna Naraiswari -; Ni Luh Gede Dian Sasmitha Diarta - (Bogor Hospitality Journal, 2025)
This study aims to identify and analyze glocalization practices in managing the Instagram account @umah_gringsing_tenganan as a strategy to build the cultural tourism image of Tenganan Pegringsingan Village, Bali. Using a descriptive qualitative approach, data were collected through in-depth interviews with the account owner and six tourists who had interacted with the account, as well as content observation and digital documentation. The findings reveal that the account effectively promotes and represents local culture by highlighting the Gringsing weaving process, traditional rituals, and daily life in the Bali Aga community. Glocalization is reflected through the use of popular hashtags, collaboration with local figures, and English language background music. However, limitations remain in the use of bilingual captions and the emotional depth of visual storytelling. Although the content is produced with simple tools, this simplicity enhances the authenticity and sincerity of the cultural narrative. The study concludes that Instagram serves not only as a promotional medium but also as a digital space for preserving local identity with global reach. These findings imply the need to strengthen content strategies through interactive educational formats and creative narratives to bridge traditional values with the expectations of a global digital audience.